Income taxes, subsidies to education, and investments in human capital - Concetta Mendolicchio; Dimitri Paolini; Tito Pietra (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2011)
We study a two-sector economy with investments in human and physical capital and imperfect labor markets. Human and physical capital are heterogeneous. Workers and firms endogenously select the sector they are active in and choose the amount of their sector-specific investments. To enter the high-skill sector, workers must pay a fixed cost that we interpret as a direct cost of education. Given the distribution of the agents across sectors, at equilibrium, in each sector there is underinvestment in both human and physical capital, due to non-contractibility of investments. A second source of inefficiency is related to the self-selection of the agents into the two sectors: typically too many workers invest in education. Under suitable restrictions on the parameters, the joint effect of the two distortions is that equilibria are characterized by too many people investing too little effort in the high skill sector. We also analyze the welfare properties of equilibria and study the effects of several tax policies on the total expected surplus. In particular, consider the equilibrium associated with a flat labor income tax. Under suitable restrictions on the parameters, a revenue neutral progressive change in the marginal tax rates is welfare improving. – – Wir untersuchen eine Zwei-Sektoren-Ökonomie mit Investitionen in Human- und physisches Kapital und unvollkommenen Arbeitsmärkten. Human- und physisches Kapital sind heterogen. Arbeiter und Unternehmen wählen endogen sowohl den Sektor, in dem sie tätig werden, als auch die Menge der sektorspezifischen Investitionen. Für Arbeiter fallen Fixkosten an, falls sie im Sektor tätig werden wollen, der ausschließlich hoch qualifizierte Arbeiter beschäftigt. Für eine gegebene Verteilung der Agenten über die Sektoren ist das Gleichgewicht dieser Ökonomie durch Unterinvestition in Human- und physisches Kapital in beiden Sektoren gekennzeichnet. Ursächlich dafür ist die Annahme, dass Investitionen nicht vertragsfähig sind. Eine zweite Ursache von Ineffzienz ist die Selbstselektion von Agenten in die beiden Sektoren: typischerweise wählen zu viele Arbeiter den Sektor für Hochqualifizierte. Zusammen bewirken diese beiden Verzerrungen, dass im Gleichgewicht zu viele Arbeiter im Hochqualifizierten-Sektor tätig werden wollen, die dabei aber insgesamt zu wenig Bildungsanstrengung in Humankapital investieren. Weiter untersuchen wir die gleichgewichtigen Wohlfahrtswirkungen von Steuern. Es zeigt sich, dass für realistische Parameterrestriktionen eine budgetneutrale progressive Änderung der marginalen Steuersätze wohlfahrtssteigernd wirkt.
Keywords: J24; H2; 330; Human capital; Efficiency; Labour income tax; Bildungsinvestition; Investition; Mehr-Sektoren-Modell; Allokationseffizienz; Einkommensteuer; Steuerwirkung; Wohlfahrtseffekt; Theorie